Fabrication of micro magnetometer using flip-chip bonding technique - Tengku Azmi, Tengku Muhammad Afif; Sulaiman, Nadzril (2017)
Magnetic field has been widely explored for its benefit towards todays development. In the early stage, the main concern was to develop a device that can detect magnetic field. Such device is called magnetometer. The advancement of technology has push the boundary even further, making a portable and robust magnetometer. Although the miniaturization of magnetometer has been widely researched and studied, the process however is not. Thus, the process governing the fabrication technique is studied in this paper. Conventional method of fabrication is known as surface micromachining. Besides time consuming, this method requires many consecutive steps in fabrication process and careful alignment of patterns on every layer which increase the complexity. Hence, studies are done to improve time consuming and reliability of the microfabrication process. The objective of this research include designing micro scale magnetometer and complete device fabrication processes. A micro-scale search coil magnetometer of 15 windings with 600μm thickness of wire and 300μm distance between each wire has been designed.